What makes us human? Augustine on interiority, exteriority and the self - John Anthony Berry (Scientia et Fides, 2017)
The composition of the human person is a central issue for Augustine. He addresses it in a philosophico-theological way; particularly in The Soliloquies and in The Confessions. What is at stake here is his exposition of “what” constitutes a person’s being human. This paper refers to some of his key ideas in this regard and attempts to identify and establish what this great thinker understands by specific terminology: the soul, the mind, and the self. His hunger for knowledge of the self helps his readers to ponder on the shifting emphasis between interiority and exteriority as well as a person’s consciousness and selfhood. Augustine wrestles with the concept of the soul, but at no point does he minimise the role of the intellect. After examining four definitions given by Augustine of the human person, this paper attempts to clarify all underpinnings related to this subject, as to be able to answer the topic in question.